Adhesive Plastic Drapes Did Not Prove to Prevent Surgical Site Infection in Total Knee Arthroplasty: A Randomized Controlled Trial - Pontoh, Ludwig Andretia Powantia; Dilogo, Ismail Hadisoebroto; Putra, Anggaditya; Widodo, Wahyu; Oesman, Ihsan; Fiolin, Jessica; Herdiman, Joshua Alward (Indonesian Hip and Knee Society (IHKS), 2024)
Surgical site infection (SSI) prevention is crucial in total knee arthroplasty (TKA) procedures. One controllable factor is preventing foreign substances from contaminating the surgical field, for which adhesive draping over surgical drapes is commonly used. To determine whether using adhesive transparent film dressing has any effect on the occurrence of SSI in TKA. We conducted a study comparing 100 TKA, divided into two groups (each with 50 participants). The first group received adhesive plastic draping during TKA, while the second group was the control. Bacterial aerobic culture swabs were taken before applying the plastic draping and after surgery following skin closure. Follow-up evaluations were conducted within one month to detect signs of SSI. The results none of the 100 TKAs included in the study yielded positive bacterial culture results. One-month post-operative evaluations revealed no signs of SSI in any of the groups.The conclusion use of adhesive plastic drapes does not provide any benefit in preventing SSI in TKA. Skin preparation, prophylaxis, and surgeon preparation protocols are more crucial for SSI prevention than adhesive plastic drapes.